2020
DOI: 10.1111/jog.14179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periodontal status in different phenotypes of polycystic ovary syndrome in untreated patients of early reproductive age: A case–control study

Abstract: Aim A few studies demonstrated an increased risk of periodontal disease in patients with polycystic ovary syndrome (PCOS). The aim of this study was to evaluate the periodontal status in women of reproductive age who were recently diagnosed with different phenotypes of PCOS. Methods This prospectively designed cross‐sectional case–control study included 116 consecutive subjects with PCOS and 90 healthy volunteers, aged between 18 and 24, who were admitted to the gynecology polyclinic between April 2018 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Out of these 19 articles which were subjected to full paper review eligibility, 7 articles were excluded as they did not address the research questions ( Supplementary Table S1 ). As a result, a final number of 12 case-control studies [ 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 33 , 34 , 35 , 36 ] met all of the inclusion and exclusion criteria and were included for qualitative synthesis ( Figure 1 ). Interexaminer reliability at the full-text screening was considered very substantial (kappa score = 1.00).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of these 19 articles which were subjected to full paper review eligibility, 7 articles were excluded as they did not address the research questions ( Supplementary Table S1 ). As a result, a final number of 12 case-control studies [ 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 33 , 34 , 35 , 36 ] met all of the inclusion and exclusion criteria and were included for qualitative synthesis ( Figure 1 ). Interexaminer reliability at the full-text screening was considered very substantial (kappa score = 1.00).…”
Section: Resultsmentioning
confidence: 99%
“…The RoB for observational studies, with Newcastle-Ottawa scale, varied across the studies, ranging from 7 to 9 stars ( Supplementary Table S2 ). After appraisal, four articles presented the highest score (9/9) [ 15 , 19 , 21 , 22 ]. Furthermore, six articles scored 8/9 [ 16 , 17 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging studies have proposed the association between PCOS and periodontitis (Kellesarian et al, 2017;Machado et al, 2020;Marquez-Arrico et al, 2020). As an essential parameter in the diagnosis of periodontitis, periodontal probing depth (PPD) was higher in PCOS in one recent cross-sectional research (Isik et al, 2020). The latest meta-analysis (Machado et al, 2020) suggested that patients with PCOS were at 28% higher odds of having periodontitis, and periodontitis increased the odds of PCOS by 46% (both P < 0.001).…”
Section: Introductionmentioning
confidence: 99%